Analysis of investment projects market in Аtyrau region (Journal of Economic Research & Business Administration, 2015)
In this paper we did a researchon the development of investment projects market, showed the general characteristics of investment projects in Atyrau region and identified the effect of investment projects on the socio-conomic development of the region. We also identified the economic and social indicators, which are affected by the volume of investment in Atyrau region. To determine and analyze the socio-economic impact of investments, we calculated the correlation coefficients, on the basis of which we identified the interrelationof statistics and interdependence of economic and social indicators, characterizing the socio-economic development of the Atyrau region. As a result, we identified that the main socio-economic indicators of the region tend to improve in the future. This conclusion is based on the fact that this region expects the implementation of big investment projects, whichwill entail not only the influx of a large amount of foreign investment, but also the development of the essential related areas of regional economies across the country as a whole.
Keywords: investment projects market; members of investment projects market; investment climate; investment potential